Transgenic zebrafish embryos to evaluate the in vivo effects of different liposome-paclitaxel nanocarrier system - Andrea Persico; Laura Molteni; Paride Mantecca; Marcelo Kravicz; Cinzia Bragato (Scientific Reports)
Abstract Zebrafish is an established valuable model for understanding the complex in vivo behavior of systemic nanocarrier strategies, their safety profile, and the array of possible compositions. To date, we have explored the possibility of Paclitaxel (PTX) delivery using liposome systems as a promising approach to treating cancer. Despite its benefits, this efficacious anti-cancer drug presents a main adverse effect, such as the onset of chemotherapy-induced peripheral neuropathy (CIPN). Thus, many research efforts are aimed at searching for the resolution or reduction of such problems. Taking advantage of zebrafish embryos, a powerful model for predicting and translating what is observed in humans, we investigated the plain PTX outcomes and compared them to the effects of different liposomes loaded with PTX. Since approximately 70% of human genes have at least one orthologue in zebrafish, studying the molecular mechanisms underlying chemotherapy-induced toxicity and increased oxidative stress becomes easy. First, we used a transgenic model to evaluate the systemic response to different concentrations of PTX, planning the final concentration to be loaded in liposomes, with and without functionalization. Then, we assessed the effects of this promising nanocarrier system at a molecular, histochemical, and behavioral level in reducing the detrimental side effects of the most successful cancer drug.